From a bio-based phosphorus-containing epoxy monomer to fully bio-based flame-retardant thermosets1. Issue 87 (20th September 2015) - Ménard, Raphaël; Negrell, Claire; Fache, Maxence; Ferry, Laurent; Sonnier, Rodolphe; David, Ghislain
<x xml:space="preserve">Abstract</x> In this work, phloroglucinol was used as a renewable resource to prepare an epoxy monomer and phosphorus containing reactive flame retardant (FR).